Healing Our Future : Leadership for a Changing Health System. - Garman, Andy (Berrett-Koehler Publishers, Incorporated, 2021)
This book is a practical, evidence-based guide to seven key leadership disciplines that will help anyone working in healthcare to pursue brighter futures.In this book, Andrew Garman looks at the major changes facing healthcare organizations and the leadership competencies required to successfully meet those challenges. He explains how people become more effective leaders over time and what science tells us works best in making this happen.At the heart of this book are seven universal disciplines--values, health system literacy, self-development, relations, execution, boundary-spanning, and transformation--which Garman divides into "enabling" and "action" disciplines. The enabling disciplines encompass the foundational work that makes leadership efforts more effective: learning more about ourselves, deepening our understanding of the world around us, and taking care of ourselves. The action disciplines describe leadership in the context of getting the work done: setting and resetting direction, collaborating inside and outside our organizations, anticipating what's coming, and helping people prepare for it. Collectively, they form an evidence-based common language of leadership that readers can easily map to any model that their organization or profession may already be using.Each chapter provides a description of the discipline, illustrates why it is important, and offers specific advice on how to raise proficiency. Appendixes offer step-by-step guidance on recruiting and engaging good mentors, along with input on developing long-term and foresight skills.